2007
DOI: 10.1080/09546630601028760
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed dye laser versus treatment with calcipotriol/betamethasone dipropionate for localized refractory plaque psoriasis: Effects on T‐cell infiltration, epidermal proliferation and keratinization

Abstract: After 8 weeks of follow-up, PDL treatment for localized and recalcitrant plaque psoriasis resulted in persistent reductions of activated and memory effector T-helper cells in the dermis, cytotoxic T cells in the epidermis, and normalization of epidermal proliferation and keratinization, in contrast to treatment with calcipotriol/betamethasone dipropionate ointment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Besides destruction of blood vessels, PDL can reduce the number of helper T cells in the dermis and cytotoxic T cells in the epidermis, and normalize epidermal proliferation, which improves the clinical signs of psoriasis vulgaris. 30,31 The pulse durations in these studies were between 0.35 and 1.5 milliseconds. [23][24][25][26][27] To date, few studies have demonstrated the efficacy of PDL on nail psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Besides destruction of blood vessels, PDL can reduce the number of helper T cells in the dermis and cytotoxic T cells in the epidermis, and normalize epidermal proliferation, which improves the clinical signs of psoriasis vulgaris. 30,31 The pulse durations in these studies were between 0.35 and 1.5 milliseconds. [23][24][25][26][27] To date, few studies have demonstrated the efficacy of PDL on nail psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…This could be because of the poor penetration of UVB in the human nail plate [ 22 ]. PDL treatment might be considered for the treatment of localized, recalcitrant plaque psoriasis, when other topical therapies have failed [ 23 , 24 ]. PDL treatment decreases the number of dermal papillary microvessels, which are important pathogenetic targets of psoriasis; PDL therapy, as it selectively targets superficial vessels, is therefore a valid therapeutic approach [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…PDL-induced selective photothermolysis of hemoglobin in vessels was one of the mechanisms of the clearance of psoriatic lesions. Apart from photothermolysis, PDL also reduced activated and memory effector Th cells in the dermis and cytotoxic T cells in the epidermis in plaque psoriasis [ 35 ], concurrent with induction of cytokine expression and collagen formation [ 36 ]. Studies about PDL treatment of hypertrophic scar have shown that PDL is strongly absorbed by hemoglobin, leading to coagulation necrosis in vessels, hypoperfusion, and local hypoxia [ 37 ].…”
Section: Pulsed Dye Laser Treatment and Its Mechanismmentioning
confidence: 99%